2008
DOI: 10.1186/1471-2458-8-50
|View full text |Cite
|
Sign up to set email alerts
|

Investigating socio-economic-demographic determinants of tobacco use in Rawalpindi, Pakistan

Abstract: Background: To investigate the socio-economic and demographic determinants of tobacco use in Rawalpindi, Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 17 publications
(13 reference statements)
9
36
1
1
Order By: Relevance
“…This finding collaborates with the study of Alam et al (2008), who have also found the similar effect of residential area on smoking in Pakistan. As reasoned by Alam et al (2008), rural dwellers are prone to have low awareness levels on the risks of smoking because of lack of anti-smoking media in the rural areas. As a result, tobacco industry may borrow this opportunity to target their sales at those rural dwellers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding collaborates with the study of Alam et al (2008), who have also found the similar effect of residential area on smoking in Pakistan. As reasoned by Alam et al (2008), rural dwellers are prone to have low awareness levels on the risks of smoking because of lack of anti-smoking media in the rural areas. As a result, tobacco industry may borrow this opportunity to target their sales at those rural dwellers.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of rural-urban comparison, Alam et al (2008), who based their study on Pakistan, find that urbanites are less likely to smoke compared to the rural dwellers. However, in the case of Germany, the effect of residential area is quite the opposite where the urban residences have higher likelihood to smoke than the rural residences (Bauer et al, 2007).…”
Section: Variablesmentioning
confidence: 99%
“…Several countries currently experience high incidences of TB and high prevalence of tobacco use and Pakistan is an illustrative example. A recent survey found that 33% of Pakistani men and 4.7% of women use tobacco on a daily basis (Table 6) (Alam et al. 2008).…”
Section: Pakistan: An Illustrative Examplementioning
confidence: 99%
“…50% being youth who are playing a major role in the spread of infectious disease like tuberculosis [6].…”
Section: Journal Of Infectious Diseases and Therapymentioning
confidence: 99%